Nutrition in Advanced Age Population - Andreevski, Vladimir; Krstevski, Gregor (Consulting and Training Center KEY, 2021)
Nutritional status of an individual is affected by genetic and environmental factors, access to nutrients, personal preferences, nutritional awareness, comorbidities and daily habits. The number of individuals aged over 65 is increasing globally. This review will look at strategies for nutritional screening and diet therapy in the elderly, taking into account phenomena that influence nutrition and commonly affect this age group. Malnutrition can be assessed via criteria that account for loss of weight, muscle and subcutaneous fat, in combination with decreased energy intake and functional status. Malnutrition and involuntary weight loss are associated with an increased mortality risk, while some studies show that voluntary weight loss reduces this risk. Malnutrition leads to a plethora of negative outcomes, and may signal dire underlying disease such as malignancy. Factors that predispose to malnutrition in the elderly include: anatomical and physiological changes of the gastrointestinal tract, endocrine system and body composition, and impairment of sight, smell and taste. Concomitant illnesses affecting the heart, lungs, liver and kidneys, and depression and dementia also negatively impact nutrition, while socio-economic changes interfere with access to food. Once identified, malnutrition can be mitigated via diet therapy which aims to tailor nutrition to the aforementioned changes, compensate any deficiencies and prevent future recurrence. Special attention should be paid to caloric, protein and fat requirements and diet supplementation with vitamin D, B12, iron and calcium. Focused nutritional assessment can aid in timely detection of malnutrition and its constituent components, which include anorexia, cachexia and sarcopenia. This also provides the opportunity to identify underlying malignancy, and systemic and psychiatric conditions. Diet therapy can then be tailored to accommodate for these conditions and to the changes known to occur in the elderly, potentially mitigating malnutrition and reducing mortality risk.
Keywords: nutrition; elderly people; diet therapy